Identification of Clinically Relevant Mycobacterial Species After Extended Incubation Times in the BACTEC MGIT System. Issue 1 (30th August 2018) - Rea, Bryan; Maisel, Julia R; Glaser, Laurel; Alby, Kevin
Abstract: Objectives: Traditionally, for mycobacterial culture both solid and broth media are used and routinely held for 6 weeks minimum to optimize yield. We retrospectively reviewed all positive mycobacterial cultures over a 12-month period to assess growth kinetics of clinically relevant isolates. Methods: From January to December 2015, 658 positive mycobacteria cultures by solid (7H11 and 7H10 plates) and/or broth (BACTEC MGIT) media were identified and reviewed. Results: In broth-only cultures, 21 of 153 (13.7%) from 21 patients were positive after 28 days' incubation. Subsequent chart review revealed the following species: 11 Mycobacterium avium intracellulare complex (MAI), five Mycobacterium tuberculosis (MTB), and five other non-MTB/MAI mycobacteria. Two of the cases of MTB were first-time isolates, and 11.4% of MTB-positive cultures became positive after 4 weeks' incubation. Conclusions: These data provide strong evidence reaffirming that clinically meaningful results are frequently detected after extended incubation times by broth-only methods, including several MTB isolates.